2017
DOI: 10.1113/jp273994
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myofiber vascular endothelial growth factor is required for the exercise training‐induced increase in dentate gyrus neuronal precursor cells

Abstract: Exercise signals neurogenesis in the dentate gyrus of the hippocampus. This phenomenon requires vascular endothelial growth factor (VEGF) originating from outside the blood-brain barrier, but no cellular source has been identified. Thus, we hypothesized that VEGF produced by skeletal myofibers plays a role in regulating hippocampal neuronal precursor cell proliferation following exercise training. This was tested in adult conditional skeletal myofiber-specific VEGF gene-ablated mice (VEGF ) by providing VEGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…Figure C shows confocal images of a representative soleus fibre immunostained for muscle stem cell markers Pax7+ and Nestin‐GFP. Nestin is a marker for quiescent muscle stem cells (Rich et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure C shows confocal images of a representative soleus fibre immunostained for muscle stem cell markers Pax7+ and Nestin‐GFP. Nestin is a marker for quiescent muscle stem cells (Rich et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Male C57BL/6J mice (10 weeks of age) were housed three to four per cage in a pathogen‐free vivarium, maintained on a 12 h:12 h day–night cycle and provided standard chow (Harlan Tekland 8604, Madison, WI, USA) and tap water ad libitum . Nestin‐green fluorescent protein (GFP) mice were generated and kindly provided by Dr M. Yamaguchi (Rich et al . 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal blood flow was substantially lower in the myofibre VEGF‐null mice (Rich et al . ), although this did not appear to result from decreased angiogenesis in the dentate gyrus, since the number of new endothelial cells (defined as CD31+/BrdU+ cells) was similar in the two groups. However, it may indicate that adequate hippocampal blood flow is a necessary prerequisite for neurogenesis.…”
mentioning
confidence: 85%
“…In agreement with this, Rich et al . () also found that the VEGF gene‐ablated mice were unable to improve their exercise performance, despite performing a similar voluntary training regime to their normal littermates.…”
mentioning
confidence: 92%
See 1 more Smart Citation